The Pictorial Fit-Frail Scale-Malay version (PFFS-M): reliability and validity testing in Malaysian primary care - Sally S., Ahip; Sazlina S., Ghazali; Olga, Theou; Azah A., Samad; Sabrina, Lukas; Ummu K., Mustapha; Mark Q., Thompson; Renuka, Visvanathan (Oxford University Press, 2022)
Background: This study investigated the reliability and convergent validity of the PFFS-Malay version (PFFS-M) among patients (with varying educational levels), caregivers, and health care professionals (HCPs). PFFS-M cutoffs for frailty severity were developed.